ปัจจัยคัดสรรที่สัมพันธ์กับการติดยาเสพติดของวัยรุ่นชายตอนต้นในกรุงเทพมหานคร - ประไพ การะเกตุ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The propose of this research was to study the selected factors related to early adolescent male drug addict in Bangkok Metropolis. The sample were 498 early adolescent male drug addict devided into 2 groups: (1) 248 early adolescent male drug addict in the hospital 1 aged 13 -15. (2) 250 Matayomsuksa 1 , 2 and 3 male adolescent students of the same aged , from White schools in Bangkok Metropolis .The research instruments were the Personal Data Questionnaire , the Parenting style Measuring Scale which were developed from Baumrind’s research, Extroversion / Introversion Inventory from Llona, J. (1997) and Coopersmith Self-Esteem Inventory- School Form (1984). The data were analyzed by the discriminant analysis technique with stepwise methods. Wilks’s Lambda was used for the entry criterion. The results showed that 4 variables from the total 13 variables accounted for 82.1 percent of the variance of group membership between early adolescent male drug addict and early adolescent male students. The 4 variables that related to early adolescent male drug addict and early adolescent male students in the Bangkok Metropolis : (1) Associate with drug addict friend (2) Education level (3) Self-Esteem and (4 ) Parent Marrige Status.